Charge-coupled device based on optical tomography system in detecting solid and transparent objects in non-flowing crystal clear water - Jamaludin J.; Rahim R.A.; Rahim H.B.A.; Rahiman M.H.F.; Rohani J.M.; Muji S.Z.B.M. (Elsevier GmbH, 2024)
Indexed by WOS/SCOPUS/ERA